Unraveling the Meaning of Proverbs: Cognitive Semantic Analysis and its Relationship to Character Education - Hermandra, Hermandra; Mustafa, M. Nur; Zulhafizh, Zulhafizh (Proceeding International Conference on Malay Identity, 2024)
This study aimed to analyze the meaning of proverbs from the aspect of cognitive semantics and their relevance to character education. This study used a qualitative research approach. The research data was documentary in nature and utilized in the life of the Malay community. The selection of proverbs was conducted by considering the uniqueness of their meanings, popularity, and relevance in everyday life. There were eight representative proverbs that serve as the basis for analysis and were relevant to character education. The analysis method employed cognitive semantics to elucidate the meaning within the selected proverbs and their relevance to character education values that can be applied at the educational unit level. The analysis of proverbs through cognitive semantic analysis revealed the presence of three types of metaphors, namely conceptual metaphors, orientation metaphors, and image schema metaphors. The values found in the proverbs were relevant to character education, it includes: responsibility, empathy, flexibility, caution, wisdom, discipline, persistence, concerns, sensitivity, hard work, cooperation, patience, awareness, equality, diligence, accuracy, openness, vigilance, consistency, respect, honor, nationalism, realism, and readiness. The values found in the proverbs can serve as a guidance and strengthen the implementation of character education at the educational unit level.